Application of fuzzy and pid algorithm in gantry crane control - Nguyen Van Dong Hai; Nguyen Thien Van; Nguyen Minh Tam (Journal of Technical Education Science, 2017)
Gantry crane (2D crane) system had been applied popularly in practice, especially in goods transportation. Fuzzy and PID algorithm are widely used in industry and had been applied successful for controlling 2D crane. This paper verifies again both Fuzzy and PID algorithms in controlling a 2D crane system. This article also proposes a fuzzy controller with four inputs and one output used to control 2D crane system. In this paper, both algorithms are proved to work well with crane model in simulation and real experiment.